Chapter Canons, books of canons, and ecclesiastical judgments in Carolingian Italy: the Council of Mantua, 827 - Heil, Michael (Reti Medievali E-Book, 2022)
The long-running jurisdictional dispute between the patriarchs of Aquileia and Grado entered a period of particular activity in the 820s, culminating in a judicial decision in Aquileia's favor at the Council of Mantua in 827. This council and its consequences offer fertile ground for exploring the ways that texts figured in ecclesiastical conflicts in ninth-century Italy. Recent work has shed light on the role hagiographical texts played in this dispute. This chapter examines another "textual" dimension: the role of canons and canon-law norms in arguments and decisions, in the "courtroom" and beyond. The chapter concludes with brief discussion of a different case, from Lucca, that shows with particular clarity the close connection that could exist between canon law in the manuscripts and in legal practice.